Common bacteria and treatment options for the acute and chronic infection of the total ankle arthroplasty. Issue 7 (October 2022) - Pfahl, Kathrin; Röser, Anke; Gottschalk, Oliver; Hörterer, Hubert; Mehlhorn, Alexander; Dolp, Patrick A.; Walther, Markus
Abstract: Background: There is little valid data available on managing infected total ankle arthroplasty (TAA). Methods: A single-center, retrospective evaluation from 20 patients with PJI (periprosthetic joint infection) of the ankle compared the bacteria isolated by preoperative arthrocentesis and intraoperative cultures to the pathogens of knee PJI. Long-term failure rates of irrigation and debridement (I&D) and polyethylene exchange, revision arthroplasty, and arthrodesis were analyzed. Results: The most common bacteria were Staphylococcus aureus and Coagulase-negative staphylococci. There was no significant difference when comparing the causing pathogens of PJI of the ankle with the knee. After a follow-up of 50, 4 months, the long-term failure rate after I&D and polyethylene exchange was 40%, and of revision was 9%. Conclusions: We concluded that the pathogenesis of PJI of the ankle and knee seems to be comparable. Regarding treatment options, we found that standardized techniques for PJIs of the knee have their limitations regarding infected TAA.